Pengaruh Level Substitusi Rumput Bothriochloa pertusa dengan Kangkung terhadap Kecernaan Bahan Kering, Kecernaan Bahan Organik, Nilai Energi dan Energi Termetabolisme secara in vitro - Fransiska Lujum; Gustaf Oematan; Grace Maranatha (Animal Agricultura, 2023)
This study aims to determine the level of substitution of Bothriochloa pertusa grass with water spinach on dry matter digestibility, organic matter digestibility, energy value and metabolized energy in vitro. This study used a completely randomized design (CRD) with 4 treatments and 4 replications. The treatments given were P0= Bothriochloa pertusa grass 60% + Leucaena 40%, P1= Bothriochloa pertusa grass 45% + Leucaena 40% + Water spinach 15%, P2= Bothriochloa pertusa grass 30% + Leucaena 40% + Water spinach 30%, P3 = Bothriochloa pertusa grass 15% + Leucaena 40% + Water spinach 45%. The variables measured were dry matter digestibility, organic matter digestibility, energy value and metabolized energy. The data obtained were analyzed using Analysis of Variance (ANOVA) and analyzed using Duncan's multiple range test. Mean KcBK P0: 46.25 ± 1.24, P1: 50.93 ± 3.68, P2: 53.33 ± 3.32, P3 64.77 ± 3.44, KcBO P0: 37.80 ± 1, 12, P1: 42.48±4.95, P2: 44.73±1.95, P3: 56.90±4.20, DE P0: 7.68±158, P1: 8.23±803, P2: 8.55±302, P3: 10.55±598, ME P0: 6.29±130, P1: 6.75±659, P2: 7.01±247, P3: 8.65±491. The results of the statistical analysis showed that the treatment had a significant effect (P<0.05) on dry matter digestibility, organic matter digestibility, energy value and metabolized energy in vitro. It was concluded that the effect of the level of substitution of Bothriochloa pertusa or the combination of Bothriochloa pertusa and water spinach increased dry matter digestibility, organic matter digestibility, energy value and energy value metabolized to energy value in vitro.